An Analysis of the Representation of Gender Inequality in the Novel Cantik Itu Luka by Eka Kurniawan: A Postcolonial Feminist Approach - Sherlina Meisya Rindu Setya Putri (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This study aims to analyze the presence of gender inequality in the novel Cantik itu Luka by Eka Kurniawan. It employs a descriptive qualitative method and the theory of postcolonial feminism. The study seeks to (1) examine and describe the forms of gender inequality experienced by female characters in the novel from a postcolonial feminist perspective, and (2) analyze the portrayal of female and male characters within the context of gender in the novel. The findings indicate that Cantik itu Luka, when viewed through the lens of postcolonial feminist theory, represents gender inequality as a structural issue rooted in the colonial era.